(Lifelong) learning in your pocket? - Christoph Igel (FernUniversität Hagen, 2014)
This article focuses on the development, deployment and use of innovative technologies to support education scenarios in schools, universities and further training. Building on the various phases of corporate learning, social learning, mobile learning and intelligent learning, the first section examines the technology usage behaviour of children, young people and (young) adults in schools, studies and teaching. This is followed by a presentation of technological developments using the technology life cycle and the consequences of the differing devel-opment states and maturity levels of technologies such as content learning management, social networks, mobile devices, multidimensional and multimodal spaces, augmented reality applications, and the internet of things, services and data for deployment and use in education scenarios. The article subsequently sets out the requirements placed on digital technologies in terms of content, didactics and methodology, of content creation, recycling, digitisation and retrievability, and of standards. A further section offers methodological guidelines for the use of digital technologies for teacher and student interaction, social interaction, collaborative authorship, commenting, evaluation and assessment. Differentiating between school and university environments, the final portion offers a summary overview of findings regarding framework conditions, influencing variables, limiting and supporting factors, and challenges in introducing and sustainably implementing digital technologies within school lessons, teaching, studies and further training.